1987
DOI: 10.1063/1.98642
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index, relaxation times and the viscoelastic model in dry-grown SiO2 films on Si

Abstract: Inert thermal anneals were performed at various temperatures to determine annealing kinetics of dry thermally grown SiO2 films on Si. Two stages of relaxation are demonstrated. The film relaxes quickly to an intermediate level, and then progresses more slowly toward full relaxation. The relaxation times to attain the fully relaxed refractive index, 1.460, and full ≤3% swelling were found to fall below typical oxidation times at T≥1150 °C, in concurrence with the experimentally observed breakpoint in the refrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
32
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 24 publications
10
32
1
Order By: Relevance
“…5,18,19 While the bulk of the oxide is a stable amorphous SiO 2 layer, 18 the region near the Si͑001͒ interface may be a transition layer, possibly stabilized by high stresses which are known to exist within the oxides 20,21 and especially at the Si/SiO 2 interface. 14 Alternatively, the layer could be a region of higher density strained silicon, where the lattice is compressed slightly in the vertical.…”
Section: ͓S0003-6951͑97͒02823-4͔mentioning
confidence: 99%
“…5,18,19 While the bulk of the oxide is a stable amorphous SiO 2 layer, 18 the region near the Si͑001͒ interface may be a transition layer, possibly stabilized by high stresses which are known to exist within the oxides 20,21 and especially at the Si/SiO 2 interface. 14 Alternatively, the layer could be a region of higher density strained silicon, where the lattice is compressed slightly in the vertical.…”
Section: ͓S0003-6951͑97͒02823-4͔mentioning
confidence: 99%
“…We consider this interpretation to be convincing in the case of thick oxides. 16 In fact, it predicts 22 an abrupt change for the activation energy of the parabolic rate constant, B, around 1100°C, which has been indeed observed 8 Uematsu et al 7 consider an alternative mechanism also related with the oxide relaxation. According to them, the oxide stress would have a higher influence on v than on the diffusivity.…”
Section: -5mentioning
confidence: 99%
“…It is known that the refractive index of thin-film SiO 2 overlayers, n,, depends on thickness, L,, oxidation temperature, T., annealing temperature, T., and time, t., index of =he substrate It has been observed that the refractive index of the SiO 2 overlayer undergoes a relaxation during annealing (22)(23)(24)(25). …”
Section: Experimental Procedures and Data Analysismentioning
confidence: 99%
“…(2) using A=1.099 and X,=92.27 (10) which corresponds to bulk SiO 2 . The observed initial rapid relaxation of the effective refractive index (23) can be attributed to the evolution of the interface, and a detailed model for this will be discussed below.…”
Section: Experimental Procedures and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation